Enrichment and description of novel bacteria performing syntrophic propionate oxidation at high ammonia level. (17th January 2021) - Singh, Abhijeet; Schnürer, Anna; Westerholm, Maria
Summary: Inefficient syntrophic propionate degradation causes severe operating disturbances and reduces biogas productivity in many high‐ammonia anaerobic digesters, but propionate‐degrading microorganisms in these systems remain unknown. Here, we identified candidate ammonia‐tolerant syntrophic propionate‐oxidising bacteria using propionate enrichment at high ammonia levels (0.7–0.8 g NH3 L −1 ) in continuously‐fed reactors. We reconstructed 30 high‐quality metagenome‐assembled genomes (MAGs) from the propionate‐fed reactors, which revealed two novel species from the families Peptococcaceae and Desulfobulbaceae as syntrophic propionate‐oxidising candidates. Both MAGs possess genomic potential for the propionate oxidation and electron transfer required for syntrophic energy conservation and, similar to ammonia‐tolerant acetate degrading syntrophs, both MAGs contain genes predicted to link to ammonia and pH tolerance. Based on relative abundance, a Peptococcaceae sp. appeared to be the main propionate degrader and has been given the provisional name " Candidatus Syntrophopropionicum ammoniitolerans". This bacterium was also found in high‐ammonia biogas digesters, using quantitative PCR. Acetate was degraded by syntrophic acetate‐oxidising bacteria and the hydrogenotrophic methanogenic community consisted of Methanoculleus bourgensis and a yet to be characterised Methanoculleus sp. This work provides knowledge of cooperating syntrophic species in high‐ammonia systems and reveals that ammonia‐tolerant syntrophic propionate‐degrading populations share common features, but diverge genomically and taxonomically from known species.